A study of determinant of Y Generation vacation preferences / Nur Hayati Nabilah Shaharani - Shaharani, Nur Hayati Nabilah (2015)
The purpose of this research is to study the determinant of Y generation vacation preferences. The factors of choice for destination (dependent variable) include cost, number of days and purpose of holidays (independent variable). A questionnaire related to these variables was constructed and 335 copy of questionnaire were distributed to Universiti Teknologi MARA (UiTM) student. The data collected for this survey were then tested by using SPSS system version 21.0 for the process of analyzing and interpreting. Pearson Correlation Matrix was used to generate output according to research question and research objectives. From the output, it shown that cost (0.927) has the highest relationship with determinant for vacation preferences and the other factor which is purpose of holidays show high relationship. This topic was chosen as the researcher wants to know what is/are the determinant/s that will influence student’s vacation preferences decision making.